2020
DOI: 10.1097/md.0000000000018569
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the avoidability of adverse drug reactions using the LAAT and modified Hallas tools

Abstract: An adverse drug reactions avoidability tool called the Liverpool ADR avoidability assessment tool (LAAT) was recently developed (for research purposes), and subsequently validated with mixed interrater reliability (IRR). We investigated the comparative IRR of this tool in an inpatient cohort to ascertain its practical application in this setting. The patient population was comprised of 44 ADR drug pairs drawn from an observational prospective cohort of patents with ADR attending a Weill Cornell Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
5
10
1
Order By: Relevance
“…This is supported by moderate interrater reliability (IRR) of between 0.4 and 0.65. The interrater agreement and consistency among raters reported from our study is in agreement with findings from recently published reports that examined the utility of the novel LAAT tool in the general patient population [ 7 , 9 ]. The result of this study demonstrates the potential for preventability of costly and mortality-prone drug-related liver injury in vulnerable elderly population especially those with multi-morbidity, although this needs to be confirmed in by prospective systematic studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is supported by moderate interrater reliability (IRR) of between 0.4 and 0.65. The interrater agreement and consistency among raters reported from our study is in agreement with findings from recently published reports that examined the utility of the novel LAAT tool in the general patient population [ 7 , 9 ]. The result of this study demonstrates the potential for preventability of costly and mortality-prone drug-related liver injury in vulnerable elderly population especially those with multi-morbidity, although this needs to be confirmed in by prospective systematic studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our result suggests that this was not the case. The percentage of EA from our study (80%) is consistent with that reported by the original developers of the tool [9], and a recent study by Danjuma et al [7]. In the study by Danjuma et al [7], the percentage pairwise agreement utilizing the LAAT and modified Hallas tools were reported as 78.5% and 62.2% respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1 Indeed, we recently reported on the utility of a novel tool (Liverpool Adverse Drug Reactions Avoidability tool [LAAT]) for identifying whether an adverse drug reaction (ADR) was avoidable or not. 3 This tool utilizes commonly recordable clinical parameters to adjudicate the preventability of development of adverse drug reactions. 4 Our comparative evaluation of the utility of this tool showed that its overall inter-rater agreement was >65% with an intraclass correlation coefficient of 0.68 (CI 0.55, 0.79).…”
Section: Dear Sirmentioning
confidence: 99%